GENDER DALAM SYARIAH : RELASI ANTARA LAKI-LAKI DAN PEREMPUAN - Handayani, Tri; Ilyas, Deddy (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
Conversation about women is not endless. Every conversation about women will occupy her position to be equal in the gender relation, but on the other hand women will occupy the lowest position, including in the the social, cultural, economic, political, and even religious fields.